Hate Crimes in Cyberspace - Danielle Keats Citron (Harvard University Press, 2014)
During the summer of 2008, â€œAnna Mayerâ€ was getting ready to begin her fi rst semester in graduate school. In her spare time, she wrote a pseudonymous blog about her weight struggles, body ac cep tance, and other personal issues. She enjoyed interacting with her readers and commenting on other blogs; it provided a support system and sounding board for her ideas. Before school began, she searched her name and found posts describing her as a â€œstupid, ugly fat whoreâ€ who â€œcouldnâ€™t take a hint from a man.â€ Anonymous posters listed her e-mail address, phone number, and dating site profi les. She received e-mails warning that the authors knew where she lived. Posters â€œoutedâ€ her as the author of her pseudonymous blog, taunting that the â€œconfessions sheâ€™s made about her pitiful fat fucking self are now blasted across teh [sic] Internet.â€1 Over the next year, the attacks grew more gruesome and numerous. Sites appeared with names like â€œAnna Mayerâ€™s Fat Ass Chroniclesâ€ and â€œAnna Mayer Keeps Hoâ€™Ing It Up.â€ Posts warned that â€œguys who might be thinking of nailingâ€ her should know about her â€œuntreated herpes.â€ A post said, â€œJust be DAMN SURE you put on TWO rubbers before ass raping Anna Mayerâ€™s ST diseased pooper!â€ Posters claimed that she had bipolar disorder and a criminal record for exposing herself in public. Racist comments she never made were attributed to her. Posts listed her professorsâ€™ e-mail addresses, instructing readers to tell them about Mayerâ€™s â€œsickening racist rants.â€ Someone set up a Twitter account in Mayerâ€™s name that claimed she fantasized about rape and rough sex. Hundreds of posts were devoted to attacking her